Exploring Feed Digestibility and Broiler Performance in Response to Dietary Supplementation of Chlorella vulgaris - Sofie Van Nerom; Kobe Buyse; Filip Van Immerseel; Johan Robbens; Evelyne Delezie (Animals)
This study evaluated the feed digestibility of diets including autotrophic Chlorella (C.) vulgaris in 252 male broilers (Ross 308), comparing unprocessed biomass (trial 1) and pulsed electric field (PEF) processed biomass (trial 2) at inclusion levels up to 20%. In trial 2, performance and meat color were also evaluated. Each trial included seven treatments (0%, 1%, 2%, 5%, 10%, 15%, and 20% (%w/w on dry matter (DM)) C. vulgaris) with six replicates (three birds per replicate) per treatment. Data were analyzed using linear, quadratic, and broken-line models. Control feeds without microalgae inclusion achieved a crude protein digestibility of 82.04 ± 1.42% (trial 1) and 81.63 ± 1.90% (trial 2), while feed with 20% non-processed microalgae inclusion only had a protein digestibility of 66.96 ± 1.16% (trial 1) and feed with PEF processed microalgae at 20% had a protein digestibility of 72.75 ± 0.34% (trial 2). In general, increasing inclusion levels of C. vulgaris impaired nutrient digestibility, significantly reducing crude protein, crude fat, gross energy, and crude ash digestibility (p < 0.001). Broken-line models identified critical inclusion thresholds beyond which digestibility declined significantly, i.e., at 10% for crude protein, 12.53% for crude fat, and 9.26% for gross energy in unprocessed microalgae feeds (trial 1). For PEF-processed microalgae, only a broken line fit was obtained for gross energy, with a breakpoint at 5% (trial 2). Furthermore, a significant linear decrease in body weight (BW) (p < 0.001), average daily gain (ADG) (p < 0.001), average daily feed intake (ADFI) (p = 0.006), and relative and absolute breast filet weight was observed as microalgae inclusion level increased (trial 2). Color parameters also changed significantly with increasing microalgae inclusion level: L* showed a significant linear decrease (p = 0.029), b* and a* showed a significant linear increase (p < 0.001) (trial 2). This research advances the exploration of sustainable protein alternatives, highlighting the potential of microalgae in broiler feed and the benefits of processing methods such as PEF to enhance nutrient utilization.